Validation of the King’s Sarcoidosis Questionnaire (KSQ) in a Dutch sarcoidosis population - van Manen, Mirjam J. G.; Wapenaar, Monique; Strookappe, Bert; Drent, Marjolein; Elfferich, Marjon; de Vries, Jolanda; Gosker, Harry R.; Birring, Surinder S.; Patel, Amit S.; van den Toorn, Leon; van den Blink, Bernt; Boomars, Karin; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
ABSTRACT Background The King’s Sarcoidosis Questionnaire (KSQ) is a brief questionnaire assessing health status using five modules (General Health Status, Lung, Eyes, Skin, Medication) in patients with sarcoidosis. The KSQ was only validated in one English sarcoidosis cohort.Objective The aim of this study was to validate the KSQ in a Dutch sarcoidosis population.MethodsThe KSQ was translated according to international guidelines and tested in interviews with patients. Consecutive outpatients completed multiple questionnaires twice, two weeks apart. Construct validity, internal consistency and repeatability were determined.Results Of the 98 patients included 85 had lung, 22 skin and 24 eye disease. There was good construct validity of the KSQ General Health Status module against the World Health Organization Quality of Life-BREF questionnaire. The Medication module correlated weak to moderate with most questionnaires. The correlations with organ-specific questionnaires varied from strong for Eyes (r=0.75), Skin (r=-0.62) to moderate for Lung (r=-0.45 with MRC breathlessness scale). Internal consistency was good for all KSQ modules (Cronbach’s α 0.72-0.93). Intraclass correlation coefficients (0.70-0.90) and Bland-Altman plots showed good repeatability of the KSQ.ConclusionThe Dutch KSQ is the first translation of the English KSQ, validated in a Dutch sarcoidosis population.